Performance analyses and evaluation of CO2 and N2 as coolants in a recuperated Brayton gas turbine cycle for a Generation IV nuclear reactor power plant - Osigwe, Emmanuel O.; Gad-Briggs, Arnold; Nikolaidis, Theoklis; Pilidis, Pericles; Sampath, Suresh (ASME, 2019)
As demands for clean and sustainable energy renew interests in nuclear power to meet future energy demands, Generation IV nuclear reactors are seen as having the potential to provide the improvements required for nuclear power generation. However, for their benefits to be fully realised, it is important to explore the performance of the reactors when coupled to different configurations of closed-cycle gas turbine power conversion systems. The configurations provide variation in performance due to different working fluids over a range of operating pressures and temperatures. The objective of this paper is to undertake analyses at the design and off-design conditions in combination with a recuperated closed-cycle gas turbine and comparing the influence of carbon dioxide and nitrogen as the working fluid in the cycle. The analysis is demonstrated using an in-house tool, which was developed by the authors. The results show that the choice of working fluid controls the range of cycle operating pressures, temperatures and overall performance of the power plant due to the thermodynamic and heat properties of the fluids. The performance results favored the nitrogen working fluid over CO2 due to the behavior CO2 below its critical conditions. The analyses intend to aid the development of cycles for Generation IV NPPs specifically Gas-cooled Fast Reactors (GFRs) and Very High-Temperature Reactors (VHTRs).
Keywords: Coolants; Gas turbines; Power stations; Carbon dioxide; Cycles; Generation IV reactors; Fluids; Closed-cycle gas turbines; Nitrogen; Nuclear power